(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Knowing the general purposes of the Shariah is necessary to properly understand the legal texts, to understand the intent of God Almighty and the intent of His Noble Messenger, and to derive rulings from their evidence in an acceptable manner, it is not sufficient for the mujtahid to know the aspects of the semantics of the meanings, rather he must know the secrets of legislation And the general purposes that the legislator intended from his legislation the various provisions so that he can understand the texts and interpret them properly, and derive rulings in the light of these general purposes. It has been proven, by induction and following the various provisions in Sharia, that its original intention is to achieve the interests of the people, preserve these interests and ward off harm from them. However, these interests are not what the person deems to be an interest for him and a benefit according to his desires. And desires, for a person may see driven by his beneficial whims is harmful, and the harmful ones are beneficial, influenced by his psychological desires and his aspiration and anticipation of easy immediate benefit, without paying attention to serious future damage, so he may see that it is beneficial for him to consume people’s money in vain by hidden and twisted methods, or by monopolizing their powers, or by taking Usury in order to increase his money in this forbidden and pernicious way, or he will abstain from jihad to enjoy the pleasures of life, and this person forgets that these benefits are mock rather than real, since they are in essence pure harm in the future and in the future. And for all of this it was necessary to explain the objectives of the general Sharia, so that the person responsible would be aware of them and know what to take and what to withhold and weigh their interests and harms with them. And it has been proven by induction that the intention of the Sharia, as we said: achieving the interests of the servants by finding them first, then by preserving them second. Since the knowledge of the objectives of Sharia is related to the science of the principles of jurisprudence, and the knowledge of the rules of jurisprudence, it is a part of them, so the mujtahid must know the secrets of legislation and the general purposes that the lawmaker intended from his legislation the various rulings to properly understand the legal texts and interpret them properly, and it is not enough to know the aspects of the indications Expressions over meanings, knowledge of the general purposes of Sharia is necessary to derive rulings from their evidence in an acceptable manner. And as we mentioned earlier, the purpose of the Sharia is to achieve the interests of the people by finding them first, then preserving them secondly. The interests that the Sharia seeks to achieve are of three types: necessities, needs, and improvements. And since it is one of the most important necessities that are among the most important interests achieved by the objectives of Sharia, including the protection of man in his life and his offspring, the Sharia has legislated the Sharia provisions that guarantee the preservation of the life of man and his society and the continuation of his offspring with cleanliness, purity and purity, and facing all aspects of challenges from epidemics, diseases and viral ailments, to survive their dangers And its causes and challenges, so Islam, in its honorable law, made multiple faces of purity, purity and cleanliness in the life of the individual, the family and society. Islam is the religion of purity and cleanliness in its fullest meanings, as it was keen on cleanliness of belief from myths and falsehood, cleanliness of the heart from polytheism, distraction, exaggeration and envy, cleanliness of the tongue from gossip and backbiting, cleanliness of the body and clothing from dirt and unpleasant odors, as well as cleanliness of the home, mosque, work, residential neighborhoods, roads, various means of transportation, and much more.